Association of Physical Function With Driving Space and Crashes Among Older Adults. (8th January 2019) - Ng, Linda S; Guralnik, Jack M; Man, Cora; DiGuiseppi, Carolyn; Strogatz, David; Eby, David W; Ryan, Lindsay H; Molnar, Lisa J; Betz, Marian E; Hill, Linda; Li, Guohua; Crowe, Christopher L; et al.
Abstract: Background and Objectives: Balancing both driver mobility and safety is important for the well-being of older adults. However, research on the association of physical function with these 2 driving outcomes has yielded inconsistent findings. This study examined whether physical functioning of older drivers, as measured by the Short Physical Performance Battery (SPPB), is associated with either driving space or crash involvement. Methods: Using cross-sectional data of active drivers aged 65–79 years from the AAA Longitudinal Research on Aging Drivers (LongROAD) study ( n = 2, 990), we used multivariate log-binomial and logistic regressions to estimate the associations of the SPPB with either self-reported restricted driving space in the prior 3 months or any crashes in the past year. Interaction with gender was assessed using likelihood ratio tests. Results: After adjustment, older drivers with higher SPPB scores (higher physical functioning) had lower prevalence of restricted driving space (8–10 vs. 0–7, prevalence ratio [PR] = 0.88, 95% confidence interval [CI]: 0.78–0.99; 11–12 vs. 0–7, PR = 0.78, 95% CI: 0.61–0.99). Fair (8–10), but not good (11–12), scores were significantly associated with reduced crash involvement (8–10 vs. 0–7, odds ratio [OR] = 0.71, 95% CI: 0.60–0.84). Gender was not a significant effect modifier. Discussion and Implications: This study provides evidence that higher physical functioning is associated with better driving mobility and safety and that the SPPB may be useful for identifying at-risk drivers. Further research is needed to understand physical functioning's longitudinal effects and the SPPB's role in older driver intervention programs.